Family aggregation of arterial hypertension - Jairo Jesús Gomez Tejeda; Manuel Ramón Pérez Abreu; Odalis Tamayo Velazquez; Aida Elizabeth Iparraguire Tamayo (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Arterial hypertension is one of the chronic diseases caused by the interaction of genetic and environmental etiopathogenic factors. Objective: To determine the existence of family aggregation of arterial hypertension. Material and Methods: A cross-sectional analytical study of cases and controls was carried out to determine the family aggregation of arterial hypertension. The universe consisted of all (257) patients diagnosed with risk factors for high blood pressure; the sample was made up of 60 patients distributed in 30 hypertensive patients (cases) and 30 patients without diagnosis (controls). The information collected was processed using the Epi info statistical software. Results: In the group of cases, first-degree relatives with history of hypertension predominated (43.9 %). In the group of controls, second-degree relatives represented the 44.1%. Bad dietary habits were presented as the most frequent risk factor in both groups with 28.7 % and 47.5 %, respectively. Patients with positive family history (OR= 1.93, p = 0.008 95 % CI = 1.18-3.16) and those suffering from obesity (OR = 9.03, 95 % CI = 2.80-29.1 p = 0.0001) were at higher risk of developing hypertension. Conclusions: The existence of family aggregation of arterial hypertension was determined.  People with first-degree positive family history of hypertension and presenting obesity were at higher risk of suffering from the disease.